Computer aided education on protection system - Shameeza Izma Sabariman (Universiti Malaysia Perlis, 2009)
Computer Aided Education (CAE) presents a host of new opportunities for institutions to improve educational outcomes. Computer aided education can be used in teaching and learning module in a whole range of ways including on protection system. This project aims is to develop a new teaching module for undergraduate students and also for those who involve directly or indirectly in power engineering system which used computer aided education (CAE) to support students’ learning. The project is designed to enhance the learning and teaching method for protection system using computer aided education. Due to the project, the protection system will be focus on the basic equipment of the protection system on power engineering system. A protection system has three basic equipments. There are instrument transformers, relay and circuit breaker. The develop software will assist students to understand about the equipments of the protection system interactively. The software is developing using Macromedia Flash 8.0.